Demand Elasticity for Local Public Transport in Polish Cities: Do Local Policies Matter? - Paweł Swianiewicz; Agata Brzóska (Transylvanian Review of Administrative Sciences, 2020)
Since 1990, the number of local public transport passengers has been steadily decreasing with a simultaneous increase in the number of residents using individual transport. Since that process has contributed to an increase in traffic congestion and the deterioration of air quality in cities, local governments have tried to reverse that negative trend. A few years now, a reversal of this trend has been observed in some cities. This article, using data on the number of passengers in over 80 Polish cities, presents regression models explaining the factors influencing the demand for public transport services, and it estimates the demand elasticity related to various independent variables. The explanatory model refers both to the features of the cities’ socio-economic environment and to the organization of the service. The results indicate that local policies matter: the density of the public transport network is the most important factor in relation to the volume of demand, while the ticket price level is almost irrelevant. Demand is also clearly increasing in the largest cities, but the relationship between demand and population size is not a linear one.